Application of Problem Based Learning Assisted By QR Code to Improve Mathematical Problem-Solving Ability of Elementary Teacher Education Students - Santoso Santoso; Himmatul Ulya; Ratri Rahayu (Universitas Tidar, 2019)
This study aims to examine the effectiveness of Problem Based Learning (PBL) assisted by QR code on students’ mathematical problem solving ability. This experimental research was carried out on students of the Elementary School Teacher Education Study ProgramUniversitas Muria Kudus in the mathematical concept course in the academic year of 2016/2017. The ability to solve mathematical problems is measured by tests. Data analysis techniques used include t-test and proportion test. The results of this study are: 1) the mathematical problem solving ability of students who learn through PBL assisted by QR code is better than the mathematical problem solving ability of students who learn through Direct Instruction learning; 2) the mathematical problem solving ability of students who are taught with PBL assisted by QR code have reached the minimum completeness criteria (MCC) and 3) the proportion of students taught with PBL assisted by QR code that has reached the MCC is better than the proportion of students studying through Direct Instruction learning that have met the minimum completeness criteria (MCC). Thus, the lecturer can develop PBL assisted by QR code to create interesting learning so that students are enthusiastic about the learning, which will have a positive effect on their mathematical problem solving ability.